Microflora associated with healthy and diseased turbot (Scophthalmus maximus) from three farms in northwest Spain - Toranzo, A. E.; Novoa, Beatriz; Romalde, Jesús L.; Núñez, S.; Devesa, S.; Mariño, E.; Silva, R.; Martínez, Emili; Figueras Huerta, Antonio; Barja, J. L. (Aquaculture, 1993)
14 páginas, 4 tablas, 3 figuras A comparative analysis of the microbiological quality of three turbot (Scophthabnus maximus) farms (A, B, and C) located in Galicia (northwest Spain) is given. The microbial load and types of bacteria in the internal organs (liver and kidney) of apparently healthy fish was monitored over a year, and all the disease problems occurring during this survey were analyzed. The percentage of healthy turbot in which positive bacterial growth was obtained was relatively high in the three ongrowing facilities. Farm A exhibited the poorest conditions of fish health with an average of 42% fish infected, while farm B showed the best microbiological quality with 27% of turbot harbouring bacteria in the internal organs. In all three farms, a wide range of bacteria was found in healthy turbot with Vibrio ( V. splendidus-V pelagius, Vjisheri-V harveyi and Vibrio spp.) and Pseudomonas spp. being the predominant groups comprising at least 80% of the total bacterial isolates in each farm. The highest number of pathological problems (22 ) with the most diverse bacterial flora occurred in farm A. Vibrio spp. and Pseudomonas spp. were the most prevalent bacteria recovered from diseased turbot. Haemorrhages in palate and jaws, tail and fins, and ulcerative lesions were the most frequent external clinical signs of diseased fish recorded in the three farms. However, it was not possible to associate a particular bacterial species with a specific pathology. Routine use in farm A of oxolinic acid and nitrofurantoin may have led to the development in the Vibrio strains of resistances to both chemotherapeutants (up to 25%). This study was supported by Grants MAR 9 l- 1133~CO2-0 1 and MAR 89- 0270 from the Comision Interministerial de Ciencia y Tecnologia (CICYT), XUGA 8030389 from Xunta de Galicia (Spain), and EUREKA project No. EU-347, between Spain and Norway. Peer reviewed